SECOND HANKEL DETERMINANT PROBLEM FOR SEVERAL CLASSES OF ANALYTIC FUNCTIONS RELATED TO SHELL-LIKE CURVES CONNECTED WITH FIBONACCI NUMBERS - Sokol, Janusz; Ilhan, Sedat; Guney, H. Ozlem (TWMS journal of applied and engineering mathematics, 2018)
In this paper, we investigate upper bounds for the second Hankel determinant in several classes of analytic functions in the open unit disc, related to shell-like curves and connected with Fibonacci numbers.Keywords: Analytic functions, shell-like curve, Fibonacci numbers, starlike functions, convex functions, Hankel determinant.AMS Subject Classification: 30C45, 30C50